Kandungan Fenolik dan Flavonoid Total Daun Macaranga hispida (Blume) Mull. Arg sebagai Kandidat Obat Antidiabetes - Megawati, Megawati; Fajriah, Sofa; Supriadi, Edi; Widiyarti, Galuh (Jurnal Kefarmasian Indonesia, 2021)
Diabetes Mellitus (DM) is one of the non communicable diseases (NCDs) with the largest number of deaths in the world. The Macaranga hispida (Blume) Mull. Arg is a source of phenolic compounds. Phenolic is grouped as polyphenols group that widely functioned as antidiabetic. The α-glucosidase enzyme plays a role in the forming of glycoproteins and glycolipids. The α-glucosidase enzyme can be used for antidiabetic activity assay because of its capability on breaking down carbohydrate into glucose in the human small intestine. This study aimed to determine phenolic content, total flavonoid content, and antidiabetic activity of M. hispida leaves extract and its fraction. The extract and fraction were tested for the phenolic levels using Folin-Ciocalteau method, the total flavonoid using alumunium chloride method, and the antidiabetic activity using α-glukosidase method. The yield of methanolic extract of the Macaranga hispida was 10.23%. Phenolic content of the ethyl acetate fraction from the methanolic extract was 8.411 mg, equivalent to gallic acid/100 mg extract. Total flavonoid content was 6.14 ± 0.31b/b μg/mL. Antidiabetic activity assay of the extract and the fractions of Macaranga hispida resulted the highest antidiabetic activity (IC50) was in the ethyl acetate fraction with IC50 value 21.91 μg / mL.